Anti-PSMA monoclonal antibody increases the toxicity of paclitaxel carried by carbon nanotubes - Comparetti, Edson José [UNESP]; Romagnoli, Graziela Gorete [UNESP]; Gorgulho, Carolina Mendonça [UNESP]; Pedrosa, Valber de Albuquerque [UNESP]; Kaneno, Ramon [UNESP] (Elsevier, 2020)
Multiple-wall carbon nanotubes (CNTs) were functionalized with polyethyleneimine in order to incorporate paclitaxel (PTX), the first line chemotherapeutic agent for prostate cancer. These particles were then covered with antibodies for the prostate-specific membrane antigen (PSMA), to address them to prostate cancer cells. LNCaP prostate cancer cells (PSMA+), HCT-116 and CaCo-2 colon cancer cells (PSMA−), as well as human peripheral monocytes and lymphocytes (PSMA−), were in vitro exposed to fluorescent CNT composites. The interaction/adherence of those composites to target cells was analyzed by fluorescence microscopy and flow cytometry, showing a diffuse interaction of CNTs and CNT-PTX with all cell types. Analysis of cytotoxicity revealed that both prostate (PSMA+) and colorectal cancer cells (PSMA−) were more susceptible to PTX complexed with CNTs than to pure PTX or CNTs alone, while the incorporation of anti-PSMA (CNT-PTX-PSMA) improved the toxicity on LNCaP cells but not on PSMA- targets. No toxicity was observed in human monocytes and lymphocytes but composites induced phenotypical changes in monocytes. Our results demonstrate the feasibility of using anti-PSMA antibody to address drug-loaded CNT to cancer cells as a strategy for improving the effectiveness of antineoplastic agents.
Keywords: Anti-PSMA; Carbon nanotubes; Chemotherapy; Nanocarrier; Prostate cancer